Pengaruh Stres Kerja Dan Kompensasi Terhadap Kinerja Guru Sdit Attaufiq Bogor - Yudi Rakhim; M Azis Firdaus; Immas Nurhayati (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
This study aims to empirically examine the effect of destructive work stress and compensation on teacher performance. The hypothesis put forward in this study is whether there is a significant effect of work stress and detachment on teacher performance at SDIT At Taufiq Bogor. The population in this study amounted to 35 teachers and the sample used was all teachers. The research data was collected using three scales, namely the Work Stress Scale, the Compensation Scale and the Teacher Performance Scale. The analysis was carried out using multiple linear regression techniques using Microsoft Excel in 2019. The results of this research analysis indicate that there is no significant effect between work stress and teacher performance as indicated by the tcount value for X1 which is smaller than t in the table (0.184 < 1 , 69). The next results show that there is a significant influence between feelings and teacher performance as indicated by the tcount value at X2 which is greater than the t value in the table (3.465 > 1.69).